DECODING YAKSHAGANA: UNVEILING THE SEMIOTIC SECRETS OF A TRADITIONAL ART FORM - S., Saran; T. G., Harikumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
From time immemorial literature and art have exercised immense fascination for those who have been endowed with aesthetic sensibility. Every art form has its origin in the basic instinct of man. As life is made varied and complex by geographical conditions, climate, ethnicity, food habits and so on, art and literature have varied manifestations. The essential basis of art is the psychic modulations of the person who creates it and enjoys it. The primary aim of all art is to impart a higher form of aesthetic experience which is an aesthetic transformation of mundane reality. India has a unique cultural tradition unparalleled in the history of any nation. Right from the beginning, Indian art and literature have been produced in accordance with the rules of aesthetics known as ‘saundarya sastara’ or ‘rasa sastara’. Indian aesthetics is a relentless stream of aesthetic exuberance. It is both a theory and practice. As a theory it has its complexities. But in practice this caters to the artistic creativity of the writer. A work of art, consciously or unconsciously follow some of the principles of Indian aesthetics. In other words, every art form can be explained in terms of one or the other of the principles of art which manifest the motive of the characters involved.